PENERAPAN METODE KONTEKSTUAL INVESTIGASI BISNIS DAN GAME ULAR TANGGA KOMBI DALAM UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR KOMUNIKASI BISNIS - Mariyaningsih, Nining (Dinamika Pendidikan, 2012)
The objective of this study is to improve studentsâ activity and studentsâ learning outcomes for accounting students in the first grade in SMK Negeri 1 Salatiga at second semester in the academic year of 2011/2012. This study was a class action research which was designed into two main cycles. Each cycle consisted of four stages started from planning, acting, observing and reflecting. The result showed that : (1) Learning activities with the above three criteria,Â  increase from 33.34% before the cycle, 66.66% in the first cycle and 93.44% in the second cycle, (2) The learning outcomes increase from 22.22% before the cycle, 75% in the first cycle and 94.44% in the second cycle. Therefore; the use of this method could be a teachersâ reference in implementing the teaching-learning process.